2015
DOI: 10.1371/journal.pone.0121536
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Pilot Partner Notification Program for New HIV Cases in Barcelona, Spain

Abstract: BackgroundAn estimated 30% of HIV cases in the European Union are not aware of their serological status. This study aimed to assess the effectiveness of a pilot HIV partner notification program.MethodsHIV cases diagnosed between January 2012 and June 2013 at two healthcare settings in Barcelona were invited to participate in a prospective survey. We identified process and outcome measures to evaluate this partner notification program, including the number of partners identified per interviewed index case, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 25 publications
1
17
0
3
Order By: Relevance
“…On the other hand, higher than study in Hawassa, Kenya and India, which was 84.1%, 61% and 77%, respectively (20,29,35). Likewise, it was higher than studies conducted in Harar, Barcelona, Peru and Burkina Faso, which was 70.6%, 70.8%, 60% and 88.1%, respectively (16,24,33,37). It is also higher than study in Gondar and Southern Ethiopia, which was 81.7% and 68.8%, respectively (43,44).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…On the other hand, higher than study in Hawassa, Kenya and India, which was 84.1%, 61% and 77%, respectively (20,29,35). Likewise, it was higher than studies conducted in Harar, Barcelona, Peru and Burkina Faso, which was 70.6%, 70.8%, 60% and 88.1%, respectively (16,24,33,37). It is also higher than study in Gondar and Southern Ethiopia, which was 81.7% and 68.8%, respectively (43,44).…”
Section: Discussionmentioning
confidence: 65%
“…An estimated 30% of HIV cases in the EU are also not aware of their HIV status (37). In Georgia during 2013 revealed that 82% of PLHIV knew their diagnosis (38).…”
Section: Introductionmentioning
confidence: 99%
“…This study shows that STI must be a priority in public health. In Barcelona, different preventive programs have been developed to try to reduce the incidence of STIs, such as a sauna program and a partner notification program [ 27 ]. We have also created 3 specialized units of STI to increase early diagnosis and reduce damage and in recent years the collaboration between public health services and community associations has enhanced for early diagnosis of STIs.…”
Section: Discussionmentioning
confidence: 99%
“…This differs from provider referral where the provider confidentially contacts and notifies the partners of their potential exposure to HIV without waiting for the index to reach out to their partners. APS has been shown to be feasible and effective in newly diagnosing HIV infected individuals in both high‐ and low‐resource settings .…”
Section: Introductionmentioning
confidence: 99%